Capability of Farmers Adaptation towards Natural Resources Vulnerability in Wajak, Malang - Utomo, Medea Rahmadhani; Hidayat, Kliwon; Handono, Setyo Yuli (IPTEK Journal of Proceedings Series, 2019)
Extreme climate is at risk of a water resource crisis. Land degradation provides challenges for farmers to switch to non-agriculture or not worked on. In cases that occur, then several problems arise including 1) how the internal conditions of the socio-ecological farmers, 2) adaptation of farmers to the crisis of water resources and 3) the role of non-agricultural work in overcoming economic uncertainty. Issues relating to the Socio Ecology System (SES) were examined by mixed methods. It is known, the type of soil on land generally is inceptisol. Mixed cropping system between cassava and cane was chosen to anticipate the loss of farmers, especially when water is difficult. The vulnerability of natural resources encourages farmers to behave creatively and adaptively in carrying out their life activities. The form of adaptation ability of farmers is to utilize the potential of dairy cattle and goat farming when agricultural land is difficult to cultivate. For those who do not have livestock, they take jobs as miners of sand and wood. Sand and wood as future savings. Various non-agricultural activities are able to support many farmers, especially for those who experience a natural resource crisis.